Parental Separation and its Relation to Children's Underachievement in Primary School Education - Odeh, Dr. Adnan; Omari, Nedaa Al- (IJRDO- Journal of Educational Research, 2017)
This study aims at investigating the relationship between parental separation (parental divorce)and the underachievement of children in the primary stage. The study sample consists of (100)children from two public schools (Mutah School for Girls and Al-Qurtubi School for Boys), theInstitution of Legal Aid and the Family Protection Center. The average includes (50) childrensuffering from the problem of separation, and (50) live in stable families in Zarqa City in Jordan. Thedata is collected from several sources: First, the pupils’ marks during the preceding two years for allthe sample members except the second-grade pupils whose marks of only one year are considered.Second, the data is collected in collaboration with home-room teachers, school records, and specialrecords of the pupils who suffer from separation problems. Third, parents of the target sample groupparticularly the incubating father or mother after separation to know about their children's educationlrecords. To answer the study questions, arithmetic means and standard deviations are used. Thestudy results reveal that there are differences with statistical significance in achievement betweenboys and girls in favor of the girls. The study results also show that there are differences withstatistical indications between stable family children and separated families in favor of the childrenof stable families, Furthermore, the results show that there is some linking relation between thepupils’ achievement and the secure and safe situation of the families where they live.